Discussion on Treatment Technologies for Mud Pumping Disease in Ballastless Track Subgrade (Journal of Global Humanities and Social Sciences, 2025)
With the rapid development of high-speed railways, ballastless track, as an advanced track structure, plays a crucial role in providing high-speed and highly stable transportation services. However, over time, issues such as mud pumping disease have emerged in ballastless track structures, posing serious threats to track stability and operational safety. To address this problem, this paper combines practical case studies to thoroughly investigate treatment technologies for mud pumping disease in ballastless track subgrades, with a focus on the application of grouting technology. The study first evaluates the effectiveness of grouting through on-site core drilling and ground-penetrating radar (GPR) detection, followed by comparative analysis to verify its efficacy in improving subgrade stability and restoring support capacity. Experimental results demonstrate that after grouting treatment, track vibration amplitude significantly decreases, train running stability improves markedly, and no new mud pumping issues are observed in subsequent inspections.